Boundary Layer Control with a Plasma Actuator Utilizing a Large GND Mesh Electrode and Two HV Electrode Configurations - Ernest Gnapowski; Sebastian Gnapowski; Paweł Tomiło (Sensors)
This article presents the results of experimental studies on the influence of the geometry of high-voltage plasma actuator electrodes on the change in flow in the boundary layer and their influence on the change in the lift coefficient. The plasma actuator used in the described experimental studies has a completely different structure. The experimental model of the plasma actuator uses a large mesh ground electrode and different geometries of the high-voltage electrodes, namely copper solid electrodes and mesh electrodes (the use of mesh electrodes, large GND and HV is a new solution). The plasma actuator was placed directly on the surface of the wing model with the SD 7003 profile. The wing model with the plasma actuator was placed in the wind tunnel. All experimental tests carried out were carried out for various configurations. The DBD plasma actuator was powered by a high-voltage power supply with a voltage range from Vp = 7.5–15 kV. The use of a high-voltage mesh electrode allowed for an increase in the lift coefficient (CL) for the angle of attack α = 5 degrees and the air flow velocity in the range from V = 5 m/s to 20 m/s, while the use of copper electrodes HV with the plasma actuator turned off and on, were very small (close to zero). The experimental studies were conducted for Reynolds numbers in the range of Re = 87,985–351,939.